2008
DOI: 10.2147/vhrm.s2063
|View full text |Cite
|
Sign up to set email alerts
|

Adherence treatment factors in hypertensive African American women

Abstract: Background: Hypertension among African American women is of epidemic proportions. Nonadherence to treatment contributes to uncontrolled blood pressure in this population. Factors associated with adherence to treatment in African American women are unknown. The purpose of this study was to identify factors associated with adherence to hypertension treatment in African American women. Methods: Five audio-taped focus groups were conducted with hypertensive African American women, 35 years and older receiving trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 14 publications
8
49
0
6
Order By: Relevance
“…American women revealed the same findings (Fongwa et al, 2008). Other barriers have been described as inaccessible health education programs regarding high blood pressure prevention and control, inadequate financial resources, inconveniently located healthcare facilities, and long wait times within those facilities (Hildreth & Saunders, 1991;Wexier, et al, 2009).…”
Section: Barriers To Blood Pressure Control In Blacks/african Americansmentioning
confidence: 79%
See 1 more Smart Citation
“…American women revealed the same findings (Fongwa et al, 2008). Other barriers have been described as inaccessible health education programs regarding high blood pressure prevention and control, inadequate financial resources, inconveniently located healthcare facilities, and long wait times within those facilities (Hildreth & Saunders, 1991;Wexier, et al, 2009).…”
Section: Barriers To Blood Pressure Control In Blacks/african Americansmentioning
confidence: 79%
“…The major barrier identified by researchers is a lack of trust in the healthcare system (Elder et al, 2012;Fongwa et al, 2008;Wexier, et al, 2009). The issue of African Americans' mistrust in the healthcare system dates back to the 1932 Tuskegee Syphilis Study during which black males were left untreated even after the discovery and availability of penicillin (Gamble, 1997).…”
Section: Barriers To Blood Pressure Control In Blacks/african Americansmentioning
confidence: 99%
“…That study used focus groups with 20 hypertensive AA women to identify 3 main categories of HBP treatment adherence factors: beliefs and knowledge about HBP, facilitators and barriers to adherence. 12 The principal investigator drafted the items and then these were reviewed by 3 experts (2 adherence-to-treatment researchers and a cardiovascular healthcare researcher). Then, 5 AA women (3 visiting the clinic for healthcare, 1 clinician at the clinic, and 1 in an academic healthcare setting) reviewed the instrument draft and were each paid $5 for their input.…”
Section: Methodsmentioning
confidence: 99%
“…However, applying the concepts in the model to hypertensive black women is crucial, as gender and role differences may influence women's attitudes and behaviors toward adherence to recommended treatment for HBP. The Hill-Levine model guided a qualitative study of factors associated with adherence in hypertensive AAwomen 12 that was the basis of the development of the culturally sensitive measure of facilitators of and barriers to adherence in AA women.…”
Section: Introductionmentioning
confidence: 99%
“…Its formulation was consolidated from international studies (17)(18)(19)(20)(21) and only one Brazilian study (22) that indicated variables that fit into this dimension. Therefore, the IVC may be a reflection of this characteristic and indicative of a gap in Brazilian literature, leaving the discussions that involve environmental aspects of adherence to hypertensive treatment with low visibility in relation to others.…”
Section: Environment Dimensionmentioning
confidence: 99%